Theater Without a Theater—Inspiring 40: The IPAG Story - Fernandez, Steven P. C., D.F.A. (Archīum Ateneo, 2018)
Excerpt: It amazes me to no end how prodigiously our theater has thrived in the last forty years without a theater building. I can only approximate the audiences (easily over a million) and the hundreds of artists and teachers who have been brought up with our theater.